Genetic deletion of Galectin-3 alters the temporal evolution of macrophage infiltration and healing affecting the cardiac remodeling and function after myocardial infarction in mice - Cassaglia, Pablo (2020)
Fil: Cassaglia, Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina